Hubungan Dukungan Suami Dengan Keberhasilan Asi Eksklusif Pada Ibu Bekerja Di Wilayah Kerja Puskesmas Lemoe Kota Parepare - Rizky Aprilia (Barongko: Jurnal Ilmu Kesehatan, 2026)
Exclusive breastfeeding coverage among working mothers remains below the expected target. One of the key factors influencing the success of exclusive breastfeeding is husband’s support, which includes emotional, informational, instrumental, and appraisal support. This study aimed to determine the relationship between husband’s support and the success of exclusive breastfeeding among working mothers in the working area of Lemoe Public Health Center, Parepare City. This research used an analytic observational design with a cross-sectional approach. The population consisted of all working mothers with infants aged 6–12 months, totaling 60 respondents, and total sampling was applied. Data were collected using a structured questionnaire comprising 20 questions on husband’s support and a dichotomous question on exclusive breastfeeding status. Data analysis was conducted using univariate analysis to describe frequency distribution and bivariate analysis using the Chi-Square test with a significance level of 0.05. The results showed that 65% of respondents received good husband support and 60% successfully provided exclusive breastfeeding. Statistical analysis revealed a significant relationship between husband’s support and exclusive breastfeeding success (p = 0.002; OR = 8.33; 95% CI: 2.50–27.80). These findings indicate that working mothers who receive good husband support are more likely to successfully provide exclusive breastfeeding. Strengthening husband involvement is essential to improve exclusive breastfeeding coverage.